Histori Perkembangan Prinsip-Prinsip Etika dan Tanggung Jawab Profesi Medis: History of The Development of Ethical Principles and Responsibility of The Medical Profession - Judi, Tjatur Ermitajani; Kusbiantoro, Dadang (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
Medical practitioners face the challenges of operational pressure and opportunities to develop according to professional ideals. Medical practitioners experience feelings of fear of guilt that erode pride, responsibility, and sense of security. The question to be answered in this study is what is the history of the development of the principles and ethics of professional responsibility of medical practitioners? The study aims to understand the principles and ethics of responsibility with the historical guidance of the burden of ethical regulation and professional responsibility of medical practitioners. The study uses a narrative literature study design with a chronological-systematic approach. The results of the study show that the ethics and responsibilities of the medical profession risk damaging trust, creativity, and opportunities for professional development. The ethical principles of the medical profession have historically encouraged efforts to help all patients in a good and correct manner, while paying attention to patients’ rights to self-determination. The results of the study are discussed and recommended in the context of the professional responsibility of medical practitioners with a more diverse view, and; a knowledge-based perspective on inappropriate paradigms that medical practitioners may face.